Pengaruh Perceived Value dan Ekuitas Merek Terhadap Niat Pembelian Produk Skincare Somethinc dengan Label Halal Sebagai Variabel Moderasi (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to examine the effect of perceived value and brand equity on the purchase intention of Somethinc skincare products, as well as to test the role of the halal label as a moderating variable. A quantitative approach was employed, using purposive sampling on 100 respondents who had purchased Somethinc products and were at least 17 years old. Data were collected through questionnaires and analyzed using Partial Least Squares (PLS).The results reveal that perceived value and brand equity have a significant positive effect on purchase intention. The halal label was found to strengthen the influence of perceived value on purchase intention but did not moderate the relationship between brand equity and purchase intention. These findings highlight the importance of perceived value and brand strength in shaping purchase intention, as well as the strategic role of the halal label in enhancing consumer confidence